2021
DOI: 10.3390/rs13091843
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Attribution of Terrestrial Snow Cover Phenology Changes over the Northern Hemisphere during 2001–2020

Abstract: Snow cover phenology has exhibited dramatic changes in the past decades. However, the distribution and attribution of the hemispheric scale snow cover phenology anomalies remain unclear. Using satellite-retrieved snow cover products, ground observations, and reanalysis climate variables, this study explored the distribution and attribution of snow onset date, snow end date, and snow duration days over the Northern Hemisphere from 2001 to 2020. The latitudinal and altitudinal distributions of the 20-year averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…where, C T is the relative contributions of T s to SOS anomalies, C P is the relative contributions of P t to SOS anomalies, and C S is the relative contributions of S c to SOS anomalies. This approach was used to quantify the contributions from climate variables to alpine vegetation green-up on the roof of the world [44], snow-cover phenology anomalies over the NH [61], and GPP anomalies in the Three North region of China [62].…”
Section: Attribution Analysismentioning
confidence: 99%
“…where, C T is the relative contributions of T s to SOS anomalies, C P is the relative contributions of P t to SOS anomalies, and C S is the relative contributions of S c to SOS anomalies. This approach was used to quantify the contributions from climate variables to alpine vegetation green-up on the roof of the world [44], snow-cover phenology anomalies over the NH [61], and GPP anomalies in the Three North region of China [62].…”
Section: Attribution Analysismentioning
confidence: 99%
“…This warming has been particularly severe in the Arctic (Collins et al, 2013; Houghton et al, 2001; Kåresdotter et al, 2021; Serreze & Barry, 2011). It has led to advanced snowmelt (Chen et al, 2021; Zhong et al, 2021) and earlier emergence of insects (Saalfeld et al, 2021), forcing animals such as shorebirds to breed and migrate earlier (Lameris et al, 2017), with one cost being lower adult survival (Rakhimberdiev et al, 2018). In general, many organisms have advanced their timing of reproduction to counter the adverse effects of the warming climate (Jenni & Kéry, 2003; Root et al, 2003; Walther et al, 2002); the taxa that have advanced the least have shown the most substantial population declines (Lameris et al, 2018; Ross et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The attribution of SCP change over the past few decades has also received extensive attention [17,18]. Several studies have shown that the distribution of and changes in SCP are susceptible to surface temperature and precipitation [19][20][21] and are greatly affected by topography [22]. However, in China, most snow cover studies are on small areas.…”
Section: Introductionmentioning
confidence: 99%